Integrating genome-wide and epigenome-wide associations for antipsychotic induced extrapyramidal side effects - Kai Yao; Johan H. Thygesen; Siobhan K. Lock; Antonio F. Pardiñas; Antonia L. Pritchard; Israa Elbashir; Abdullah Lodhi; Zain-Ul-Abideen Ahmad; Michael C. O’Donovan; Michael J. Owen; James T. R. Walters; David St Clair; et al. (Psychopharmacology, 2026)
Rationale Antipsychotic medications are the first-line treatment for schizophrenia. Around 40% of people who are treated with antipsychotics could develop extrapyramidal side-effects (EPSE) including: (1) Dyskinesia, (2) Parkinsonism, (3) Akathisia, and (4) Dystonia. Objectives This study aimed to identify genetic risk factors for EPSE presence following antipsychotic treatment. Methods We conducted Genome-wide association (GWAS) and Epigenome-wide association (EWAS) meta-analyses of EPSE, with subset analyses separating first and second generation antipsychotic (FGA/SGA) exposure. We integrated significant EWAS findings from a between-case design to a comparable GWAS for association enrichment. We investigated whether polygenic risk scores (PRS) for schizophrenia, Parkinson’s disease, and Lewy-body dementia could predict EPSE. Results The primary GWAS top SNP rs2709733 (A/G) ( p = 5.755 × 10 −07 ) mapped to a long intergenic non-protein coding RNA, LINC01162 with consistent effects across all cohorts. Subset analyses with distinct FGA exposure indicated suggestive genes such as NAV2 , NRG3 , LSAMP and SGA exposure indicated SHISA9 and CNBD1 which are relevant for schizophrenia, autism, and epilepsy. In our primary EWAS, the most significant differentially methylated position (DMP) was cg05599348 (3.181 × 10 −07 ), located at chrX:103,174,718 (hg19) mapping to TMSB15B . Comparing EPSE cases to healthy controls, we identified nine DMPs associated with EPSE. The DMP cg12044923 (chr2:241453995, hg19), located within the STK32B gene, showed significant enrichment for EPSE association (permutation p = 0.010). STK32B is relevant to both psychiatric and movement disorders, suggesting potential shared mechanisms. Conclusions Our study sheds new light on the potential biological mechanisms underlying EPSE development in schizophrenia, highlighting the importance of exploring both methylation changes and SNP associations.

Comparison of CellSearch versus Parsortix circulating tumor cell enumeration and molecular characterization: A pilot study in metastatic prostate cancer patients - Jenna Kitz; Kelly Seto; Pinki Nandi; Paul Smith; David Englert; Ayten Hijazi; Michael Lock; Glenn S. Bauman; Scott Ernst; Ricardo Fernandes; Alison L. Allan (Next Research, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Oxidative stress induced by potassium bromate exposure results in altered tight junction protein expression in renal proximal tubule cells - Alice Limonciel; Anja Wilmes; Lydia Aschauer; Robert Radford; Katarzyna M. Bloch; Tara McMorrow; Walter Pfaller; Joost H. van Delft; Craig Slattery; Michael P. Ryan; Edward A. Lock; Paul Jennings (Archives of Toxicology, 2012)

Transcriptomic alterations induced by Ochratoxin A in rat and human renal proximal tubular in vitro models and comparison to a rat in vivo model - Paul Jennings; Christina Weiland; Alice Limonciel; Katarzyna M. Bloch; Robert Radford; Lydia Aschauer; Tara McMorrow; Anja Wilmes; Walter Pfaller; Hans J. Ahr; Craig Slattery; Edward A. Lock; et al. (Archives of Toxicology, 2012)

l -2-Chloropropionic acid metabolism and disposition in male rats: relevance to cerebellar injury - Ian Wyatt; Michael Farnworth; Andrew J. Gyte; Edward A. Lock (Archives of Toxicology, 1997)

The role of glutathione in L -2-chloropropionic acid induced cerebellar granule cell necrosis in the rat - I. Wyatt; Andrew Gyte; Michael G. Simpson; Peter S. Widdowson; Edward A. Lock (Archives of Toxicology, 1996)

Chloropropionic acid-induced alterations in glucose metabolic status: possible relevance to cerebellar granule cell necrosis - Edward A. Lock; Andrew Gyte; Peter Widdowson; Michael Simpson; Ian Wyatt (Archives of Toxicology, 1995)